Comparative effectiveness of traditional and non-traditional storytelling on the observational learning among grade 4 students of Krus na Ligas Elementary School - Tanyag, Riel Jane P. (School of Library and Information Studies, University of the Philippines Diliman, 2013)
To help libraries with children's literature collection and services weigh the various benefits and considerations on the use of traditional and non-traditional storytelling, an experimental study about the comparative effectiveness of the two mentioned storytelling methods is conducted. The research mainly concentrates on the influential characteristics of traditional and non-traditional storytelling to the observational learning grade school students, focusing on the four elements of Bandura's theory: attention, retention, reproduction, and motivation. Storytelling attributes that would make storytelling more appealing to students are also taken into account.